Provision of urban environmental amenities A policy toolkit for inclusiveness - Farrow, Katherine (OECD Publishing, 2022)
Environmental amenities provide a range of direct and indirect benefits in cities, and amenity provision often figures within policy portfolios to advance sustainability in urban areas. As environmental pressures and urban populations increase, it will be necessary to find ways to ensure that environmental policies do not contribute to existing inequalities in these areas. This report synthesises empirical research on the impact of environmental amenities on housing prices, examines implications on housing affordability, and offers perspectives on how negative impacts can be mitigated. The report finds that the provision of environmental amenities tends to raise housing prices, which reduces affordability, especially among renters and low-income households with reduced access to mortgages. The report concludes that there is scope to accompany amenity provision with complementary measures to mitigate distributional impacts and outlines policy avenues in that regard
Keywords: Environment